Revision of the western Nearctic spider genus Cybaeina including the description of Neocybaeina gen. nov. and Rothaeina gen. nov. (Araneae: Cybaeidae: Cybaeinae) - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2023)
This paper is the last in a series revising the Nearctic Cybaeinae spider fauna (Araneae: RTA clade: Cybaeidae) exclusive of Cybaeozyga Chamberlin & Ivie. The forested habitats of the west coast of North America are home to a diverse array of endemic Cybaeinae spider taxa. Many of these have very restricted distributions, especially within an area of the western United States of America from the Olympic Peninsula of northwestern Washington to the northern half of the California Floristic Province of California, a well-known biodiversity hotspot. Here we revise the genus Cybaeina Chamberlin & Ivie recognizing three species: the type species Cybaeus minutus Banks (= Cybaeina minuta (Banks)), C. confusa Chamberlin & Ivie, and a single new species C. dixoni Bennett spec. nov. We describe Neocybaeina Bennett gen. nov. with type species Cybaeina xantha Chamberlin & Ivie (= Neocybaeina xantha (Chamberlin & Ivie) comb. nov.) and a single new species N. burnetti spec. nov. Finally we describe Rothaeina Bennett gen. nov. with type species Cybaeina sequoia Roth (= Rothaeina sequoia (Roth) comb. nov.) and four new species R. beaudini Bennett spec. nov., R. jamesi Bennett spec. nov., R. mackinleyi Bennett spec. nov., and R. petersoni Bennett spec. nov. In addition to descriptions of the genera and both sexes of their included species (except for N. burnetti spec. nov. and R. beaudini Bennett spec. nov. which are known from females only), we provide diagnoses, illustrations, distribution maps, and, for the three species of Cybaeina and the five of Rothaeina gen. nov., identification keys. In closing, we discuss conservation implications for this cryptic and infrequently collected group of western Nearctic Cybaeinae, several of which are short-range endemic species.